Right Ventricular Dysfunction Impairs Effort Tolerance Independent of Left Ventricular Function Among Patients Undergoing Exercise Stress Myocardial Perfusion Imaging. (November 2016) - Kim, Jiwon; Di Franco, Antonino; Seoane, Tania; Srinivasan, Aparna; Kampaktsis, Polydoros N.; Geevarghese, Alexi; Goldburg, Samantha R.; Khan, Saadat A.; Szulc, Massimiliano; Ratcliffe, Mark B.; Levine, Robert A.; Morgan, Ashley E.; et al.
Abstract : Background—: Right ventricular (RV) and left ventricular (LV) function are closely linked due to a variety of factors, including common coronary blood supply. Altered LV perfusion holds the potential to affect the RV, but links between LV ischemia and RV performance, and independent impact of RV dysfunction on effort tolerance, are unknown. Methods and Results—: The population comprised 2051 patients who underwent exercise stress myocardial perfusion imaging and echo (5.5±7.9 days), among whom 6% had echo-evidenced RV dysfunction. Global summed stress scores were ≈3-fold higher among patients with RV dysfunction, attributable to increments in inducible and fixed LV perfusion defects (all P ⩽0.001). Regional inferior and lateral wall ischemia was greater among patients with RV dysfunction (both P <0.01), without difference in corresponding anterior defects ( P =0.13). In multivariable analysis, inducible inferior and lateral wall perfusion defects increased the likelihood of RV dysfunction (both P <0.05) independent of LV function, fixed perfusion defects, and pulmonary artery pressure. Patients with RV dysfunction demonstrated lesser effort tolerance whether measured by exercise duration (6.7±2.8 versus 7.9±2.9 minutes; P <0.001) or peak treadmill stage (2.6±0.9 versus 3.1±1.0; P <0.001), paralleling results among patients with LV dysfunction (7.0±2.9 versus 8.0±2.9; P <0.001|2.7±1.0 versus 3.1±1.0; P <0.001 respectively). Exercise time decreased stepwise in relation to both RV and LV dysfunction ( P <0.001) and was associated with each parameter independent of age or medication regimen. Conclusions—: Among patients with known or suspected coronary artery disease, regional LV ischemia involving the inferior and lateral walls confers increased likelihood of RV dysfunction. RV dysfunction impairs exercise tolerance independent of LV dysfunction.